The Engagement of Higher Educational Institutions in Regional Development An Overview of the Opportunities and Challenges - Goddard, John (OECD Publishing, 2008)
Across the OECD, countries, regions and higher education institutions (HEIs) are discovering each other. More and more partnerships are being established based on a growing appreciation of shared interests. This paper explores the drivers behind such engagement, from both HEI and regional development perspectives, the barriers to effective working and how these barriers are being addressed in practice in a variety of regional and national contexts. The paper concludes with suggestions as to how capacity for joint working between HEIs and regions can be enhanced through generic changes in policy and practice at the institutional, regional and national level
Keywords: Education